The origins of the teaching accounting in russian universities: Lecturer and researcher stepan usov (1797-1859) - Nazarov, Dmitry; Sidorova, Marina (De Computis, Revista Española de Historia de la Contabilidad., 2021)
The authors of the paper explore the life and professional activity of Stepan Mikhailovich Usov (1797-1859), as well as his views on the theory and practical implementation of new accounting techniques in agriculture. Usov was a talented researcher, an expert in agricultural sciences, political economy, history, and the publisher and editor of a number of Russian magazines. He worked hard all his life to disseminate knowledge about progressive technologies of agronomy and farm bookkeeping. Usov became one of the first lecturers in accounting, which he taught at St. Petersburg University in 1836 and this is in the focus of the study. Based on the Actor–network theory of Bruno Latour (ANT), the authors contribute to the previous literature within biographical studies and accounting education by identifying Usov’s role in the development of Russian accounting as a mediator in the network of educational institutions, which transformed accounting into a university discipline.